Isolation and identification of some dermatophytes causing Tinea - K.Abbass , Yass (University of Thi-Qar Journal of Science, 2015)
The study was included collection of 200 samples (100 samples of skin scales , 79 samples of hairs and 21 samplesof nails) , from patient suffering Tinea . The number of positive samples for culture were 102 sample at ratio 51% ,male form at ratio 53.9% and 46.1% for female. Five dermatophytes species were identified: Microsporum canis(41.75%) , Trichophyton verrucosum (36.89%) , T. violaceum (16.50%) , M. persicolor (3.88%) and M. gypseum (0.97%). Tinea capitis was the most dermatophytosis infection with ratio 39.5% , followed by Tinea corporis (26%) ,then Tinea faciei (12.5%) , Tinea unguium (10.5%) , Tinea cruris (5%) , Tinea pedis (4.5%) , Tinea manum (1.5%),finally Tinea barbae (0.5%) . The high percentage of infection of Tinea capitis , Tinea corporis , Tinea faciei andTinea cruris were within males , while females had a high percentage of infection with Tinea unguium , Tinea pedisand Tinea manum. The stage of age( ≤10) occupied high percentage of Tinea capitis , Tinea corporis and Tinea faciei.